Praktik Penjualan Akun Netflix Sharing Premium Ilegal dalam Perspektif Hak Cipta - Putri, Made Dhea Mulya; Kosasih, Johannes Ibrahim; Putra, I Made Aditya Mantara (Verdict: Journal of Law Science, 2025)
The development of digital technology has transformed the way people consume entertainment content, including through streaming services such as Netflix. Under copyright law, Netflix is protected as a computer program. However, the unclear definition and lack of classification related to computer programs in Law Number 28 of 2014 on Copyright create legal uncertainty regarding the protection of streaming applications. This study examines copyright protection for the Netflix application in relation to the illegal sale of shared premium accounts, as well as the legal consequences arising from such practices. The research employs a normative legal method with a statutory and conceptual approach. The findings indicate that Netflix is protected internally through its Terms of Use and externally under Law Number 28 of 2014, which prohibits commercialization without the authorization of the copyright holder, as well as Law Number 1 of 2024, which criminalizes illegal access. The legal consequences of the illegal sale of Netflix accounts include the cancellation of sale and purchase agreements, potential claims for damages by Netflix, and the possibility of account suspension for buyers. In conclusion, the public should possess legal awareness in respecting intellectual property rights, particularly copyright, by refraining from purchasing and using illegal Netflix accounts. Such conduct not only violates existing legal regulations, but also generates negative impacts in the form of losses for creators or rights holders.